SEJARAH DAN PERKEMBANGAN IKHWANUL MUSLIMIN DI MESIR - Diva Nadia Lestari; Nidaurohmah Nidaurohmah; Isna Nur Septiana (Adisam Publisher, 2025)
The purpose of writing this article is to increase insight into the history and development of the Ikhwanul muslimin in Egypt. The method used in this research is using library research sourced from books, journals and other sources that are related to the history and development of the Ikhwanul muslimin in Egypt. The discussion of this related article is to discuss the history of the formation of the Ikhwanul muslimin in Egypt, the development of the Ikhwanul muslimin in Egypt, where there are 4 phases in its development, including the pioneering phase, the training and development phase, the training and struggle phase, and the revolutionary phase. This article also discusses the characteristics of the Ikhwanul muslimin movement, as well as the influence of the Ikhwanul muslimin political movement in Egypt. The founding figure of the Ikhwanul muslimin movement, namely Hasan al-Banna, was the founding figure of this movement in Egypt in 1928. The Egyptian government, which was previously a monarchical state, was at that time led by King Faruk, who involved the Ikhwanul muslimin movement at the time of planning the coup. against the Egyptian government.